Synergetic and charge transfer properties of a metal oxide heterojunction: Photocatalytic activities - Abebe, Buzuayehu (Frontiers in Catalysis, 2022)
Improvement in the synthesis techniques and their optimum properties is the up-to-date global need for industrially-scalable applications. The sol-gel solution combustion synthesis (SG-SCS) approach is an easy, time-/energy-efficient, and creates regularly ordered porous materials that have significance in the ion-/mass-transport phenomenon. Besides, the approach also yields a decent heterojunction once optimized via HSAB theory. Forming a heterojunction also tunes the crucial properties of the materials, thus, boosting photocatalysis ability through charge transfer or/and synergistic roles. From the stability investigation results, the calcination temperature of 500 oC is determined to be ideal. The X-ray diffraction and high-resolution transmission electron microscopy (HRTEM) techniques confirmed the nanoscale size of the NPs and NCs. The porous nature of the materials is revealed from the scanning electron microscopy micrographs and BET analysis; consistent results are also noted from selected area electron diffraction and HRTEM. The detected stacking faults on the IFFT image of HRTEM also confirmed the porous properties of the NCs. The precise elemental composition and local heterojunction within Zn/Fe(III)/Mn(III) oxides were confirmed in the HRTEM, X-ray photoelectron spectroscopy, and energy-dispersive X-ray studies. The significant charge transfer capability of the NCs than bare ZnO was evidenced from the electrochemical analysis. The NCs were also effective on acid orange 8 (AO8) and congo red (CR) dyes degradation.